Pembelajaran Jarak Jauh dan Pengaruhnya Terhadap Implementasi Standar Kurikulum Pendidikan Tinggi - Umar Bin Abd Aziz (Jurnal Adabiya, 2022)
The implementation of social distancing policy as one of prevention strategies for Corona Virus Disease 2019 (Covid-19) has been directly impacted public services such as education services. During the social distancing period, the government implemented distance learning policy for schools and higher education as regulated by four Join Miniterials Decree. The shift from classroom learning method to distance learning method influences the Learning Process Standard specifically the Semester Learning Plan. Of eight national standards provided for higher education by Permenristek Dikti No. 44 /2015 regarding National Standard for Higher Education, the standard (c) Learning Process Standard and its component of Semester Learning Plan were significantly affected by the change of the method. By using six distance learning models provided in this investigation, it is discovered that not all the learning plan components affected by the change, depend on the learning model choosen. Significant adjustment are needed for subjects contain practices, laboratory exercise and skill-oriented lessons. While the normative components of the learning plan such as name of department, name of lecturer/teacher, general output and list of reference materials may not need any adjustment.